Hubungan Pengetahuan Kepala Keluarga tentang Demam Berdarah Dengue dengan Sikap Kepala Keluarga dalam Pemberantasan Sarang Nyamuk di Kelurahan Sudajaya Hilir - Ady Waluya; Adisti Oktaviaris (Fakultas Kesehatan Universitas Muhammadiyah Sukabumi, 2021)
The high incidence of DHF can also be caused by low public knowledge about DHF. Sukabumi City is one of the city areas with quite high numbers. In 2017 there were 361 cases. Meanwhile, in 2018 there were 239 cases. Dengue Hemorrhagic Fever (DHF) is an infectious disease mainly affecting children, characterized by high heat, bleeding and can cause an outbreak. By doing 3M Plus activities, which are draining, closing, and burying and other activities that can inhibit the breeding of Aedes Aegypti mosquitoes.The study used a type of collegial research with a cross sectional approach. The population consisted of all family heads in the downstream sudAjaya sub-district of 725 households. Samples were taken as many as 225 families by cluster random sampling. The instrument used in this study is a questionnaire, the data obtained is processed using chi square test statistics.The results showed that there was a relationship between the knowledge of the head of the family regarding Dengue Hemorrhagic Fever (DHF) and the attitude of the head of the family in the Eradication of Mosquito Nests (PSN) (p-value 0.022).Conclusion, there is a relationship between the knowledge of the head of family about Dengue Hemorrhagic Fever (DHF) with the attitude of the head of the family in the Eradication of Mosquito Nest (PSN).